2018
DOI: 10.15344/2456-8171/2018/135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anti-oxidants on Oxidative Stress: Assessing MDA in Urine Samples

Abstract: urine, gateway tests for Vitamin C deficiency, calcium status, adrenal stress, bio-impedance assessment and heart rate variability). Supplements were to be taken on an empty stomach. Subsequently their urine samples were tested for MDA levels again.The length of period was determined by the following factors: •When a client started the protocol. A patient may do the test on day 1 and only start the protocol after day 10.We could only measure them at the subsequent visit.• Some clients visited our clinic from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Another study reported that the abdominal Numerous oxygenated compounds, mainly aldehydes such as MDA, are produced during the attack of free radicals on membrane lipoproteins and PUFA. Assay of MDA is probably the most common method for the measurement of lipid peroxidation [50] . This is revealed that there was a significant increase in the levels of MDA and the significant decrease in hepatic SOD, CAT and GSH in the obese rats.…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported that the abdominal Numerous oxygenated compounds, mainly aldehydes such as MDA, are produced during the attack of free radicals on membrane lipoproteins and PUFA. Assay of MDA is probably the most common method for the measurement of lipid peroxidation [50] . This is revealed that there was a significant increase in the levels of MDA and the significant decrease in hepatic SOD, CAT and GSH in the obese rats.…”
Section: Resultsmentioning
confidence: 99%
“…It was noted that it had increased in all rat brain regions after aspartame consumption and had serious effects on cellular functions [12]. It produces mediators such as MDA which is a valid biomarker for oxidative stress [13]. One of the main components of the antioxidant factors in living cells is GSH.…”
Section: Discussionmentioning
confidence: 99%
“…7 MDA is claimed to become more mutagenic, then tumorigenic and also more reactive. 8 The simple and cost-effective process makes MDA routinely used for clinical analysis. 9 MDA in plasma, serum and urine samples has been used as a biomarker of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%